Open source publishing: design tools for designers - Pedro Amado (2007)
If the design thinking is correct, the tools should be irrelevant (Type) designer Pedro Amado is amongst many other things initiator of TypeForge, a website dedicated to the development of 'collaborative type' with open source tools. While working as design technician at FBAUP, he is about to finish a MA with a paper on collaborative methods for the creation of art and design projects. When I e-mailed him about open font design and how he sees that developing, he responded with a list of useful links, but also with: "Developing design teaching based on open source is one of my goals, because I think that is the future of education." This text is based on the conversation about design, teaching and software that followed.